Językowa kreacja matki w Nad Niemnem Elizy Orzeszkowej - Skorupska-Raczyńska, Elżbieta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
A content analysis of the E. Orzeszkowa’s Positivist novel Nad Niemnem [On the Niemen] makes it possible to indicate a number of different mother-types featured in the book and created by its author, namely: the Polish Mother, the caring cat mother, the cuckoo-type mother, the mother in absentia and the willow mother. The type of the Polish Mother (an ideal of patriotic motherhood, Polish: Matka Polka, the Polish Mother was the secular equivalent of the Holy Mother) is epitomized in Maria Kirłowa, earnestly and wisely devoted to her children. She runs and manages the household single-handedly, is a guardian of the home, and all alone raises her children and prepares them to live in the society of the latter half of the nineteenth century. Another mother, Andrzejowa Korczyńska, a proud Polish patriot, makes a rather monumental figure. Living a life full of ideals and rich promises, this widow seems to provide a model of proper motherhood to be followed, but, being alienated in thefamily and her social environment, is eventually a failure and she fails in life. Her son takes advantage of her, knowing that she is ready to do everything for him no matter what happens, like a cat-mother. The mother-cuckoo is represented by Starzyńska, who chooses her personal interests over the importance of family and her children, Janek and Antolka, and lets somebody else raise them. The reason behind her behavior is the need for remarrying, apparently stronger than her maternal feelings. The mother in absentia, i.e. one that is virtually non-existent in the process of the education and development of her children, is self-concentrated and self-obsessed Emilia. In this particular case, the role of Witold and Leonia’s mother is taken over by Marta, who – like a willow-mother – raises them, feeds them, educates, consoles and pampers them, not forgetting, however, about being a demanding and controlling guardian. Most of all, however, she is always there and is always ready to assist them. The novel, set in the complicated reality of the challenging second half of the nineteenth century, is a moving reminder how restrictive women’s standing was and how this situation influenced the woman’s family duties as well. These responsibilities were viewed and executed by contemporary mothers differently and had a different meaning for them, which is very eloquently presented in Eliza Orzeszkowa’s realistic novel.